Integrative transcriptomic analysis of pancreatic islets from patients with prediabetes/type 2 diabetes - Mencucci, Maria Victoria (2020)
To identify new transcriptomic alterations in pancreatic islets associated with metabolic dysfunctions in people with prediabetes (PD)/type 2 diabetes (T2D).